Development of an Ecopedagogical-Based Science Learning E-Module to Support the Adiwiyata Program at SD Negeri 01 Padang Laweh: Pengembangan E-Modul Pembelajaran IPAS Berbasis Ekopedagogik Dalam Mendukung Program Adiwiyata di SD Negeri 01 Padang Laweh - Lenna Diana Sari; Ahmad Ilham Asmaryadi; raimon efendi (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
Elementary Natural and Social Science (IPAS) learning continues to face challenges, including the limited availability of contextual digital teaching materials, the lack of integration between ecopedagogical principles and the Adiwiyata Program, and low student engagement during the learning process. This study aimed to develop an ecopedagogy-based IPAS e-module to support the implementation of the Adiwiyata Program at SD Negeri 01 Padang Laweh. The study employed a Research and Development (R&D) approach using the 4-D development model (Define, Design, Develop, and Disseminate). The research participants consisted of expert validators, fifth-grade teachers, and fifth-grade students at SD Negeri 01 Padang Laweh, while the limited dissemination stage was conducted at SD Negeri 05 Padang Laweh. The research instruments included validation sheets, practicality questionnaires, observation sheets, and learning achievement tests. Data were analyzed using descriptive quantitative analysis based on product feasibility percentages. The results indicated that the developed e-module achieved a validity score of 93.16%, categorized as highly valid. The practicality test showed teacher responses of 100% and student responses of 88.43%, both classified as highly practical. Furthermore, the effectiveness test demonstrated 100% learning mastery during both the implementation and limited dissemination stages. These findings indicate that the ecopedagogy-based IPAS e-module meets the criteria of validity, practicality, and effectiveness, making it suitable as a digital learning resource to support contextual IPAS learning while strengthening the implementation of the Adiwiyata Program in elementary schools.